Nutritional water productivity of hot chilli (capsicum annuum) under infection with meloidogyne javanica and meloidogyne incognitarace 2 - Ramputla, Mogwale Janet (My University, 2019)
Nutritional water productivity (NWP) is an assessment tool, which describes the amount of water that has been used to produce selected mineral malnutrition (MMN) elements and micronutrient malnutrition (MNMN) substances. Therefore, it links agricultural production to human nutrition. Deficiencies in MMN elements and/or MNMN substances in human nutrition referred to as malnutrition, had been linked with fatal diseases. Agricultural soils could be affected by soil-borne pathogens such as plant-parasitic nematodes, which could limit the availability of MMN elements and MNMN substances. In some communities, vegetable crops, including chilli are regarded as a major source of MMN elements and MNMN substances. Effects of root-knot (Meloidogyne species) nematodes on NWP of chilli (Capsicum annuum L.) have not been documented. The objective of the study was to determine the effects of increasing population densities of M. incognita race 2 and M. javanica on the NWP of hot chilli plants. A microplot trial was conducted at the Green Biotechnologies Research Centre of Excellence (GBRCE), University of Limpopo, South Africa. Pots were filled with 10-L steam-pasteurised (300oC) sandy clay loam soil sourced from GBRCE and Hygromix-T (Hygrotech, Pretoria North) growth medium in the ratio 3:1 (v/v). Thereafter, three-week-old hot chilli cv. 'Serrano' seedlings were transplanted into each pot, with inoculum prepared by extracting eggs and second-stage juveniles (J2) of M. incognita race 2 and M. javanica from roots of grown nematode susceptible tomato cv. 'Floradade' (Solanum lycopersicum L.) in a 1% NaOCl solution. Fourteen days after transplanting, treatments 0, 50, 125, 250, 625, 1250 and 2000 eggs and second-stage juveniles (J2) of M. incognita race 2 and M. javanica were separately inoculated using a 20 ml plastic syringe into 5-cm-deep holes in pots. At 56 days after the initiation of the treatments, Meloidogyne species xiv decreased soil pH and increased organic carbon, contributing 29 and 43% in total treatment variation (TTV) of the respective variables. Treatment effects caused the pH to decrease. NWP variables against increasing nematode numbers exhibited quadratic relations, with coefficients of determination ranging from 59 to 86% for M. incognita race 2 trial and 80 to 98% for M. javanica trial. Meloidogyne species population densities against plant variables did not show any significant relationship, except for root galling and chlorophyll content where treatments contributed 76, 98 and 47% TTV of the respective variables. Generally, root galling increased with increase in Meloidogyne species population densities, whereas chlorophyll content decreased with increasing inoculum levels. Nematode variables against their increasing population exhibited quadratic relationship with the model explained by 44 to 95% for M. incognita race 2 and 28 to 82%, association, respectively for M. javanica. In conclusion, Meloidogyne species interfered with NWP of mineral elements in chilli plant and therefore, nematode management practices should be done to reduce the nematode population densities that would confer quality to agricultural produce for human health benefits.
Thesis (M.Sc. Agriculture (Soil Science)) -- University of Limpopo, 2019
Keywords: Javanese root-knot nematode; Nutritional water productivity; Nematodes; Capsicum annuum; Soilborne plant pathogens; Javanese root-knot nematode; Plant nematodes; Capsicum annuum